Coinfection With Influenza A Virus and Klebsiella oxytoca: An Underrecognized Impact on Host Resistance and Tolerance to Pulmonary Infections - Lee, Kayla M.; Morris-Love, Jenna; Cabral, Damien J.; Belenky, Peter; Opal, Steven M.; Jamieson, Amanda M. (Frontiers in Immunology, 2018)
Pneumonia is a world health problem and a leading cause of death, particularly affecting children and the elderly. Bacterial pneumonia following infection with influenza A virus (IAV) is associated with increased morbidity and mortality but the mechanisms behind this phenomenon are not yet well-defined. Host resistance and tolerance are processes essential for host survival during infection. Resistance is the host’s ability to clear a pathogen while tolerance is the host’s ability to overcome the impact of the pathogen as well as the host response to infection. Studies have shown that IAV infection suppresses the immune response, leading to overwhelming bacterial loads. Other studies have shown that some IAV/bacterial coinfections cause alterations in tolerance mechanisms such as tissue resilience. In a recent analysis of nasopharyngeal swabs from patients hospitalized during the 2013-2014 influenza season, we have found that a significant proportion of IAV-infected patients were also colonized with Klebsiella oxytoca, a gram-negative bacteria known to be an opportunistic pathogen in a variety of diseases. Mice that were infected with K. oxytoca following IAV infection demonstrated decreased survival and significant weight loss when compared to mice infected with either single pathogen. Using this model, we found that IAV/K. oxytoca coinfection of the lung is characterized by an exaggerated inflammatory immune response. We observed early inflammatory cytokine and chemokine production, which in turn resulted in massive infiltration of neutrophils and inflammatory monocytes. Despite this swift response, the pulmonary pathogen burden in coinfected mice was similar to singly-infected animals, albeit with a slight delay in bacterial clearance. In addition, during coinfection we observed a shift in pulmonary macrophages toward an inflammatory and away from a tissue reparative phenotype. There was only a small increase in tissue damage in coinfected lungs as compared to either single infection. Our results indicate that during pulmonary coinfection a combination of seemingly modest defects in both host resistance and tolerance may act synergistically to cause worsened outcomes for the host. Given the prevalence of K. oxytoca detected in human IAV patients, these dysfunctional tolerance and resistance mechanisms may play an important role in the response of patients to IAV.